Reduction of phosphates in sewage using kiln ash. Issue 1 (September 2021) - Mahmood, D; Adnan, A.
Abstract: Phosphate is among few chemicals that abundantly occur in both soil and water environments at relatively high concentrations, and it is responsible for the promoted growth of algae in a phenomenon called eutrophication. Hence, many studies have been conducted to assess the ability of various treatments to remove phosphates from sewage. Recently, it has been discovered that phosphorus recovery may be accomplished by filtering the water. The cost of the filtering materials, on the other hand, is prohibitively expensive. As a result, current research has concentrated on utilising low-cost ones to minimise the expense of filtering. Steel production residues, such as kiln bottom ashes, are being utilised in this study to recover phosphates from contaminated wastewater. A variety of operational settings have been investigated in order to obtain the highest possible extraction efficiency at the lowest feasible cost. The results of this study showed 0.53 g/L of bottom ash needed not more than 40 minutes to reduce the phosphate concentration from 5 to 4.51 mg/L. Additionally, the results were modelled with an R2 value of more than 0.9, confirming the agreement between the theoretical and experimental results.